Theory and method in higher education research. Volume 3 - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald Publishing Limited, 2017)
Theory and Method in Higher Education Research provides a forum specifically for higher education researchers to discuss issues of theory and method. This latest collection includes discussion of a variety of theories, including; complex systems theory, organisational identity, curriculum theory, knowledge management framework, evaluation-based decision-making, and the market-university. It also includes a number of chapters focused on methods, including mixed methods and virtual ethnography, as well as a chapter situated between theory and method on the network paradigm. This latest volume presents a truly international approach with contributions from Argentina, Belgium, Canada, the Czech Republic, Finland, Germany, Norway, Portugal, the U.K. and the U.S. to provide an important contribution to international debates regarding the application and development of theory and methodology in researching higher education that will be relevant to researchers globally.
Prelims -- The guiding role of theory in mixed-methods research: combining individual and institutional perspectives on the transition to higher education -- Higher education research: looking beyond new public management -- An analytical framework for evaluation-based decision-making procedures in universities -- The study of the academic profession - contributions from and to the sociology of professions -- A developmental perspective on organizing for social responsibility: a framework of wise action for higher education organizations -- Organizational identity of universities: a review of the literature from 1972 to 2014 -- The university as an adaptive resilient organization: a complex systems perspective -- The role of curriculum theory in contemporary higher education research and practice -- A knowledge management framework for institutional research -- The differentiated market-university structural differences among university's commodification processes -- Virtual ethnography: the logistical and ethical challenges of bringing higher education research online -- The network paradigm in higher education -- Disability and college students: a critical examination of a multivalent identity -- Informal learning in the workplace: approaches to learning and perceptions of the context -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Education, Higher -- Research; Education -- Research; Higher & further education, tertiary education